2009
DOI: 10.1186/cc7350
|View full text |Cite
|
Sign up to set email alerts
|

Arterial catheter-related infection according to the catheter site

Abstract: Introduction There is considerable uncertainty about the reproducibility of the various instruments used to measure dyspnea, their ability to reflect changes in symptoms, whether they accurately reflect the patient's experience and if its evolution is similar between acute heart failure syndrome patients and nonacute heart failure syndrome patients. URGENT was a prospective multicenter trial designed to address these issues. Methods Patients were interviewed within 1 hour of first physician evaluation, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…24 Such was the case in our control group, similar to published reports, 16,33,34 and much lower than reported by Esteve et al, 15 where improper handling of connectors was reported as a risk factor. The rate of blood culture contamination was similar to that reported by halm et al 35 In our trial, and in keeping with Koh et al, 36 increased manipulation of the arterial catheter by repeated blood extractions did not increase infection rates; however, this was a risk factor associated with infection by Rijnders.…”
Section: Discussionsupporting
confidence: 71%
“…24 Such was the case in our control group, similar to published reports, 16,33,34 and much lower than reported by Esteve et al, 15 where improper handling of connectors was reported as a risk factor. The rate of blood culture contamination was similar to that reported by halm et al 35 In our trial, and in keeping with Koh et al, 36 increased manipulation of the arterial catheter by repeated blood extractions did not increase infection rates; however, this was a risk factor associated with infection by Rijnders.…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion, our contribution confirms the results of recent and large studies [5,6] reporting higher rate of colonization of peripheral arterial catheters inserted in critically ill patients via the femoral route. However, when the requirement for the best hemodynamic signal outweighs the infectious risks, the femoral route should be favored.…”
supporting
confidence: 82%
“…Peripheral arterial catheters are widely used internationally and routinely inserted in the operating theatre (OT) for continuous haemodynamic monitoring and to provide convenient access for frequent arterial blood gas (ABG) analysis during major surgery (Harley 2000). Approximately, 8 million and 2Á5 million arterial catheters are inserted in the USA and Europe, respectively, each year for major surgery and critical care, with comparative widespread use in Australia (Gardner 1990, Scheer et al 2002, Lorente et al 2006, Australian Institute of Health & Welfare 2009). In spite of this extensive and well-documented global use of arterial lines, research about their management has not matched their universal application.…”
Section: Introductionmentioning
confidence: 99%